Proceedings of the 5th International Conference on the Durability of Concrete Structures 2016
DOI: 10.5703/1288284316142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Concrete Moisture Condition on Half-Cell Potential Measurement

Abstract: The detection of on-going corrosion is one of the main issues during inspection of reinforced concrete structures. The half-cell potential measurement method is the most common and established non-destructive technique to support this task. But a lot of infrastructures are exposed to rain or seawater which can cause heterogeneous moisture condition within one component. In turn this can have influence on the potential mapping results and as a consequence the interpretability of the half-cell potential measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…A numerical study by Kessler and Gehlen [47] found that inhomogeneous moisture content below the concrete surface measured can reduce the detectability of reinforcement corrosion, and suggests evaluating HCP data only from parts of the structure with similar moisture conditions [48,49].…”
Section: Combining Ndt Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A numerical study by Kessler and Gehlen [47] found that inhomogeneous moisture content below the concrete surface measured can reduce the detectability of reinforcement corrosion, and suggests evaluating HCP data only from parts of the structure with similar moisture conditions [48,49].…”
Section: Combining Ndt Methodsmentioning
confidence: 99%
“…The procedures integrate conventional test methods and are inspired by existing methodologies in the literature [22,45]. They include analyzing the HCP data from areas with comparable moisture conditions [48,49].…”
Section: Procedures For Inspection and Assessment Of Pretensioned Girdersmentioning
confidence: 99%
See 1 more Smart Citation
“…HCP measurements can be impacted by various parameters which can result in incorrect interpretations of the data. One such factor is the moisture content, which was shown to reduce electrical resistivity and lead to lower (more negative) HCP values [1][2][3][4][5][6][7]. Another crucial parameter is the concrete cover thickness, which affects the distribution of the potential, causing the potential at the steel/concrete interface to be significantly different from the potential on the concrete surface as the concrete cover thickness increases [8].…”
Section: Parameters Affecting the Hcpmentioning
confidence: 99%